Kepemimpinan Transformasional Kepribadian Proaktif dan Desain Kerja sebagai Prediktor Perilaku Kerja Inovatif - Iffah Fitri Nur Khasanah; Fathul Himam (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
Every country needs innovation to support economic growth and prepare for the future of a better nation. This study aims to empirically examine transformational leadership, proactive personality, and work design in driving innovative work behavior. The hypothesis proposed is transformational leadership, proactive personality, and work design is a predictor of innovative work behavior in employees. This study used a quantitative survey approach.  Four scales were used namely the scale of innovative work behavior, transformational, proactive personality, and work design. Data were analyzed using multiple regression techniques. The results showed that transformational leadership, proactive personality, and work design together improve employee innovation (F) = 58,032, R2 = 0,593).